IMPROVEMENT OF THE STATE CONTRACT SYSTEM: CAUSES OF PROBLEMS AND WAYS OF THEIR SOLUTIONS - D. Shatsky (Вестник университета)
The article analyzes the practice of constructing and implementing the state contract system, reflecting the established principles of public administration, the mentality and characteristics of the population of the country. The legal field of the Federal Law № 44 FZ «On the contract system in the sphere of procurement of goods, works and services for provision of state and municipal needs» is considered in terms of problems hampering the effective procurement process (staffing problem, quality problem of delivered goods and corruption problem). The mechanisms and measures necessary for an integrated solution of the above problems are identified.